OPTIMALISASI PROMOSI UMKM MELALUI PEMBERIAN LABEL KREATIF DI DESA ROWO GEMPOL - Nurissyarifah; Lilis Aliyatuz Zahroh; Nabila Rahman Khiorun Nisa’; Mila Hariani; Amir Bandar Abdul Majid; Eli Masnawati; M Sifa Fauzi Yulianis; Muhammad Yusron Maulana El-Yunusi (Abdi Jurnal Publikasi, 2025)
The implementation of UMKM labeling to provide taste or interest by looking at the labels that have been prepared by the service teams for UMKM Rowo Gempol Village Pasuruan, using the ABCD (asset based communities development) method, seeing from the sales location is quite crowded and from several markets are very interesting and many opportunities because es jaran sellers are very rarely sold by UMKM. The implementation of this labeling took place at the Ngopak Market, Lekok District, Pasuruan, with the aim of further increasing the development of UMKM in Pasuruan. Great opportunities are actually wide open for UMKM Rowo Gempol Village if the promotion strategy is carried out properly. Developing a distribution network, both locally and internationally, can be one way to expand the market. The implementation of the promotion strategy through the creation of product banners and stickers has had a significant impact on increasing the visibility and competitiveness of UMKM in Rowo Gempol Village. , the evaluation conducted after the activity showed that the use of visual promotional media such as banners and stickers had a positive long-term impact. Rowo Gempol Village's UMKM products are now better known, not only locally but also among consumers from outside the region who are interested in the unique and quality products from this village